A donor polymer based on 3-cyanothiophene with superior batch-to-batch reproducibility for high-efficiency organic solar cells. Issue 10 (15th September 2021) - Yuan, Xiyue; Zhao, Yunli; Zhan, Tao; Oh, Jiyeon; Zhou, Jiadong; Li, Junyu; Wang, Xiaojing; Wang, Zhiqiang; Pang, Shuting; Cai, Ping; Yang, Changduk; He, Zhicai; et al.
Abstract : A donor polymer based on 3-cyanothiophene, a structurally simple unit, is synthesized for organic solar cells, which exhibited prominent power conversion efficiency and excellent batch-to-batch reproducibility in a wide molecular weight range. Abstract : The realization of high-efficiency organic solar cells (OSCs) relies largely on donor polymers. However, high-performance donor polymers are limited to a handful of building blocks, which usually suffer from lengthy synthesis and high production cost. Moreover, most donor polymers exhibited strong batch-to-batch variation. Herein, we report a new building block, 3-cyanothiophene (CT), which features a very simple asymmetric structure and facile synthesis. The donor polymer (PBCT-2F) based on the CT unit realized a remarkable power conversion efficiency (PCE) of 17.1%. More importantly, PBCT-2F exhibited excellent batch-to-batch reproducibility. The six polymer batches with molecular weights ranging from 18 to 74 kDa produced very similar PCEs: 15.9–17.1% and 12.7–13.2% when the polymer was blended with Y6 and IT-4F, respectively. These results suggest the great potential of PBCT-2F for industrial synthesis and large-scale manufacturing of OSC modules. This work also demonstrates the bright future of CT units for constructing high-performance donor polymers.